The Impact of Using Learning Applications on the Cognitive Abilities of School-Age Children - Putri, Agustin Andhika; Kaya, Cemil; Kara, Sevda; Nampira, Ardi Azhar (World Psychology, 2025)
The use of digital learning applications has become increasingly prevalent in educational settings, offering a range of interactive tools designed to enhance student engagement and learning outcomes. As technology continues to influence education, it is essential to explore its impact on children’s cognitive abilities, particularly in school-age children. Learning applications are believed to improve cognitive functions such as memory, attention, problem-solving, and critical thinking. However, empirical evidence regarding the effects of these applications on children’s cognitive development remains limited. This study aims to investigate the impact of using learning applications on the cognitive abilities of school-age children. A quasi-experimental design was employed, involving 200 school-age children aged 6-12 years. The children were divided into an experimental group, using learning applications for 12 weeks, and a control group, which continued with traditional learning methods. Cognitive abilities were assessed before and after the intervention using standardized tests measuring attention, memory, and problem-solving skills. The results indicated that children in the experimental group showed significant improvements in cognitive abilities compared to the control group, particularly in memory and problem-solving skills. The study concludes that the use of learning applications positively influences cognitive development in school-age children, providing evidence for the integration of digital tools in educational practices to support cognitive growth.